Determination of the effect of topical application of N-acetylcysteine on the recovery rate of patients with chronic rhinosinusitis after surgical treatment, based on SNOT-22 test scores - Falko , Anton; Naumenko , Oleksandr (The Ukrainian Scientific Medical Youth Journal, 2023)
endonasal endoscopic sinus surgery ( FESS ) is the gold standard for the treatment of patients with chronic rhinosinusitis worldwide. The task of the otorhinolaryngologist is aimed at restoring the function of the osteomyetal complex . However, the tactics of the postoperative period, especially the topical form of treatment, remain an extremely important issue. The purpose of the study: Determination of the influence of the topical form of N-acetylcysteine on the speed of recovery of patients after FESS, compared to standardized topical treatment, based on the sino-nasal outcome test. The study was carried out at the Department of Otorhinolaryngology of Bogomolets National Medical University on the basis of the Oleksandriv Clinical Hospital of Kyiv together with the CNME "Kremenchuk City Hospital of Planned Treatment", Kremenchuk. A population of 96 patients aged 18 to 60 with a diagnosis of chronic rhinosinusitis after surgical treatment. The randomization method was two groups of patients were formed. 1st group (study) - 47 patients who received irrigation of the topical form of N-acetylcysteine. 2nd group (control) - 49 patients who received topical therapy using irrigation of 0.9% NaCl solution. The volume of surgical intervention of both groups of the study: Endonasal endoscopic maxillotomy, septoplasty , bilateral vasotomy of the lower nasal turbinates. To participate in the study, all participants had to sign an informed consent. All patients were surveyed using the SNOT22 test on the 1st day before surgery treatment and on the 3rd, 10th and 28th days after surgical treatment.According to the obtained results, the effectiveness of both methods of topical treatment was revealed (p=0.001). However, the use of topical N -acetylcysteine in patients of the study group has more effective dynamics of symptoms, according to the SNOT -22 questionnaire on the 3rd (p=0.034), 10th (p=0.002) and 28th day (p=0.001) after surgical treatment. Therefore, the topical form of N-acetylcysteine has an effective effect on the speed of recovery of the mucous membrane of the nasal cavity and paranasal sinuses and improves the quality of life in patients with chronic rhinosinusitis after FESS.